Analisis Kesulitan Dalam Menyelesaikan Persamaan Nilai Mutlak Menggunakan Model Pembelajaran Discovery Learning Untuk Siswa Kelas X SMK Negeri II Kota Tambolaka (Indo-MathEdu Intellectuals Journal, 2023)
The purpose of this study was to determine the difficulty in solving the absolute value equation using the Discovery Learning learning model for grade X students of SMK Negeri 2 Tambolaka City.  This type of research is a descriptive qualitative method, which means that the data in the study is in the form of sentence structure obtained from test results, interviews and ducumentation. The subjects of the study were 10 grade X students of SMK Negeri 2 Tambolaka City and three people were randomly selected to be interviewed. Data analysis techniques are Data obtained in this study in the form of data on absolute value test results and interview results. After the data is collected, data reduction is carried out which aims to focus on the things to be researched, namely analyzing the answers of students who have been selected as research subjects. The results showed that the overall percentage of student test results contained 3 types of difficulties carried out by students, namely concept difficulty 80%, principle difficulty 50%, verbal difficulty 50%. The impact of these difficulties is that students do not relearn the material that has been given during learning and do not pay attention to researchers delivering the material